Uji Antioksidan Belimbing Wuluh dan Ampas Nanas Terhadap Kualitas Minyak Goreng Habis Pakai - Siti Mardiyah (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2021)
Anti-Oxidant Tests of starfruit and pineapple pulp on the quality of Used Cooking Oils   ABSTRACTUsed Cooking Oil is oil produced from frying residue and is carcinogenic because it causes oxidation, hydrolysis, and polymerization to produce toxic peroxides and free fatty acids that are difficult for the body to digest. Measurement of oil quality can be measured through 3 parameters, namely, the peroxide number, the acid number and the oil color. Efforts to control the quality of cooking oil are the addition of natural antioxidants, starch wuluh and pineapple pulp. Starfruit contains flavonoids, terpenoids, phenols and pectins as well as Vitamins C and A which can absorb free radicals in oil. Meanwhile, pineapple pulp contains high levels of vitamin C, flavonoids and polyphenols which can eat free radicals. This Research aims to determine the differences in the antioxidant power of starfruit and pineapple pulp to maintain the quality of used cooking oil. This research is experimental, which will study the antioxidant power of starfruit and pineapple pulp at the acid number, peroxidant and color intensity of used cooking oil. 3 grams of dry starfruit and 0.4 grams of dried pineapple pulp are added to each pad 100 mL of used cooking oil. The application of starfruit and pineapple pulp in used cooking oil had a significant effect on the 3 oil quality parameters, namely the acid number, the peroxide number and the oil color intensity, with a significance value of P <0.05. This is because the antioxidant content and composition of the two ingredients are different. Wuluh starfruit in the addition of 3 grams provides a fairly large antioxidant effect, while pineapple pulp at a concentration of 0.4 grams has shown anti-oxidant power so a higher concentration is needed to produce optimal antioxidant power. Keywords: Antioxidants, Starfruit, Pineapple Dregs